New uses hydrogel as compensation bolus and to fill air cavities. (September 2016) - Perez-Garcia, H.; del Castillo, A.; Miguel, D.; Andrés, C.; Agulla, M.; Alonso, D.; de Frutos, J.; Pérez, C.; Torres, R.
Abstract : Introduction: Electron beams over an irregular surface produce localized hot and cold spots in the underlying medium due to scattering. This fact usually reduces the quality of the treatments. In practice, such sharp dose edges may be smoothed with an appropriately shaped bolus which has similar properties to the tissue when it is irradiated. Purpose: To present hydrogel (by Varihesive® ConvaTec) as a compensation bolus for clinical treatments Materials and methods: Hydrogel material is radiologically characterized by a CT images using a clinical TC GE HiSpeed Nx/I. HU are measured and Percentage Depth Dose (PDD) is predicted by Eclipse TPS using the Analitytical Anisotropic Algorithm (AAA) v.11.0.31 in water and hydrogel. PDD is measured in water and hydrogel with a Ross chamber (PTW) and compared with previous results (characterized HU-to-ED calibration curves were needed). A practical case of hydrogel use is shown in a vulva cancer treatment: filling skin folds. Results: Measured PDD and calculated PDD are very similar to each other. Obtained results show hydrogel and water have equivalent dosimetric properties. In the clinical case analyzed, hydrogel is shaped to the curvature of the patient's skin where the conventional laminar bolus is not able to cover. Conclusion: Hydrogel and water are radiological equivalent materials. Hydrogel can be used as a compensation bolus or to fill air cavities. Disclosure: No conflicts of interest to declare.